Pengaruh kombinasi pupuk NPK dan ekstrak kecambah kacang hijau terhadap pertumbuhan dan hasil tanaman kubis bunga (Brassica oleraceae var. Botrytis L.) - Hamdan Drian Adiwijaya; Tita Kartika Dewi; Ria Andela (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
This study aims to determine the effect of the combination of NPK fertilizer and bean sprout extract (BSE) on the growth and yield of cauliflower plants and to determine the right dose of the combination of NPK fertilizer and bean sprout extract, so as to provide maximum results on the growth and yield of cauliflower plants in the lowlands. The experiment was carried out in Pusakanagara District, Subang Regency, West Java Province. With an altitude of 15 m above sea level, the air temperature ranges from 270C–300C. The experiment was carried out from October to December 2022. The study used an experimental method and a randomized block design with four treatments and six replications. The treatment consisted of P0: 5 g NPK (as control), P1: 5 g NPK + 75 g/L, P2: 5 g NPK + 100 g/L, P3: 5 g NPK + 125 g/L. The results showed that all treatments of a combination of NPK fertilizer and bean sprout extract had a significant effect on plant height (14 and 28 days after planting(DAP)), number of leaves (14, 28, and 35 DAP), leaf diameter (14 and 35 DAP), flower weight and flower diameter. For the P3 treatment, the combination dose of 5 g of NPK fertilizer and 125 g/l of bean sprout extract had a significant effect and showed the highest yield on plant height, number of leaves, and the highest weight of cauliflower, namely 379.25 g/plant. It can be concluded that the administration of bean sprout extract (BSE) was proven to increase the growth and yield of cauliflower varieties PM 126F. Doses of bean sprout extract fertilizer up to 125 mg/L of water are considered quite effective in efforts to increase the growth and yield of flower cabbage variety PM 126F.